Metal staples in the construction of the central building of the Belvoir fortress (Kokhav Ha Yarden, Israel) - Laurent D’Agostino (Medievalista, 2023)
The archaeological study of the central building of the Belvoir fortress has revealed that a great number of iron staples were used in the construction of the exterior facings. Beside the fact that this unusual process required an exceptionally high supply of metal for this specific work, the reasons for such an execution raise questions. The central building of Belvoir castle was constructed according to a regular square plan around the courtyard, flanked in the corners by four square towers and a porch tower in the middle of the west façade. The staples are observed only on the exterior facings of the peripheral walls of the keep and the towers, at the level of the basalt embankments. Questions relating to the site first affect the distribution of these staples and their role in the construction: they are not only present at the level of the arrow-slits, which they consolidate, but also more regularly with each siding course of the embankments and near the quoining blocks connecting the towers to the central building. These clues tend to demonstrate a constructive and structural role of staples.